Cauliflower for sale in Rovaniemi, Finland in June, 2018 ... - Campbell, Sandy (University of Alberta Library, 2018)
This cauliflower was for sale in the K Supermarket in Rovaniemi, Finland, near the Arctic Circle in June, 2018. It was priced at 3.49 Euros/kilo. ...